The Laundry Care LCA project - Zuin, Stefano; Dengin, Vsevolod; Perzolla, Valentina; Bisaro, Francesca; Pipita, Mario Michele; Azzano, Alberto; Garzena, Fabio; Stabon, Elisa (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The fashion industry is increasingly scrutinized for the environmental footprint it generates. Despite this, less attention is placed on the possibility to reduce part of this footprint thanks to attitudes and daily actions that users can take in their homes. A life cycle assessment of three selected garments was performed to analyze the potential environmental benefits of an extended usage of garments thanks to the utilization of different washing treatments. Results showed that the garment production phase has consistently the highest impact. Within the use stage, the relevance of wash cycles was investigated by comparing various cycles in both the European and North America regions, and by highlighting the contribution of different energy mixes and detergent types. The data demonstrated that washing machine users can reduce the impact of garments by, for example, washing them at lower temperature, as this results in slower deterioration. Therefore, the environmental impacts per wear of garments can be reduced by around 50% by doubling the expected number of garments uses.